Retrospective evaluation of refeeding syndrome in cats: 11 cases (2013–2019). Issue 10 (October 2021) - Cook, Simon; Whitby, Emily; Elias, Neus; Hall, Georgina; Chan, Daniel L
Objectives: The aim of this study was to describe the clinicopathological findings, management and outcome of cats with refeeding syndrome (RS) following prolonged starvation. Methods: Records from four referral hospitals were searched between May 2013 and November 2019 and retrospectively evaluated. Inclusion criteria were the presence of a risk factor for RS, such as severe weight loss or emaciation following a period of presumed starvation, hypophosphataemia or a delta phosphorous exceeding 30% reduction following refeeding, being treated on the basis of a clinical diagnosis of RS and one or more derangement of hypokalaemia, hypoglycaemia or hyperglycaemia. Results: Eleven cats were identified, which had been missing for a median of 6 weeks (range 3–104 weeks). Mean ± SD percentage weight loss was 46% ± 7% (n = 8). Eight of 11 cats developed hypophosphataemia with a mean delta phosphorous of −47% ± 9%. All cats were documented to be hypokalaemic. During hospitalisation, 10/11 cats developed hyperglycaemia and 7/11 cats developed hypoglycaemia. Cardiovascular, gastrointestinal and neurological signs were common. Eight of 11 cats displayed new or progressive neurological deficits after refeeding, including mentation changes and cerebellar dysfunction. All cats became anaemic and seven cats required a blood transfusion. Eight cats survived to discharge after a mean of 14 ± 4 days of hospitalisation. Six cats developed acute kidney injury (AKI; International Renal Interest Society stage 1). The presence of AKI ( P = 0.024) was associated with non-survival and maximum bilirubin concentration was significantly higher in non-survivors ( P = 0.018). Conclusions and relevance: Cats with RS in this cohort had been missing, presumed starved, for more than 3 weeks. In addition to hypophosphataemia and hypokalaemia, altered glucose homeostasis and organ damage involving the liver and kidneys were common. Cats with RS appear to have a good prognosis, but prolonged intensive care is required.